The Legal System Governing the Execution of Administrative Contracts - Wissam Sabbar Al-Hamdani, Lect. Dr. (lark, 2024)
The union of the wills of the contracting parties and the administrative nature of the contract constitute the sources of the privileges that the administration enjoys in executing administrative contracts. Some privileges arise from clauses included in the contract that fall outside the scope of ordinary law. The administration's privileges in this case are derived from the contract itself, which produces its effects just as a private law contract produces its effects. Thus, the administration remains within the contractual field as long as its privileges result from the mentioned clauses. However, other administrative privileges do not originate from the contract but rather from its administrative nature and the rules established by jurisprudence. This is evidenced by the fact that some extraordinary clauses, which go beyond ordinary law, apply to the contract whether they are included or not. For example, the administration has the authority to terminate the contract at any time if the public utility it serves no longer justifies its continuation. The administration’s privileges are primarily aimed at securing or facilitating the mission of the public service, and the enshrinement of this lofty goal grants the administration exceptional powers or privileges. These allow it not only to exercise a form of extraordinary oversight during the implementation stages but also, under certain conditions, to unilaterally modify some contract clauses. In return for these privileges, jurisprudence has emphasized certain rights for the contractor with the administration, establishing theories and principles that allow the contractor to claim compensation for any damages incurred and ensure the contract’s execution.
Keywords: Administrative contract, administrative law, management authority